Influence of solvents on the bond strength of resin sealer to intraradicular dentin after retreatment - Marcelo PALHAIS; Manoel Damião SOUSA-NETO; Fuad Jacob Abi RACHED-JUNIOR; Mariana Carvalho de Andrade AMARAL; Edson ALFREDO; Carlos Eduardo Saraiva MIRANDA; Yara Teresinha Corrêa SILVA-SOUSA
Abstract This study evaluated the removal of filling material with ProTaper Universal Rotary Retreatment system (PTR) combined with solvents and the influence of solvents on the bond strength (PBS) of sealer to intraradicular dentin after canal reobturation. Roots were endodontically treated and distributed to five groups (n = 12). The control group was not retreated. In the four experimental groups, canals were retreated with PTR alone or in combination with xylol, orange oil, and eucalyptol. After filling material removal, two specimens of each group were analysed by SEM and µCT to verify the presence of filling remnants on root canal walls. The other roots were reobturated and sectioned in 1-mm-thick dentin slices that were subjected to the push-out test. Data were analysed by two-way ANOVA and Tukey's test (α = 0.05). SEM and µCT analysis revealed that all retreatment techniques left filling remnants on canal walls. The control group (3.47 ± 1.21) presented significantly higher (p < 0.05) PBS than the experimental groups. The groups retreated with PTR alone (2.59 ± 0.99) or combined with xylol (2.54 ± 0.77) and orange oil (2.32 ± 0.93) presented similar bond strength (p > 0.05), and differed significantly from the group with eucalyptol (1.89 ± 0.63). The solvents reduced the PBS of the sealer to dentin and no retreatment technique promoted complete removal of filling material.